MORAL MESSAGE ON THE VIDEO JOURNALIST CLIP “YURA YUNITA- TUTUR BATIN”: (Charles Sanders Peirce Semiotics Analysis) - Fahri Fidali Purba; M.Yose Rizal Saragih (LP2M IAI Nazhatut Thullab Sampang, 2022)
Abstract: This research discusses the moral message contained the video clip Yura Yunita entitled Tutur Batin. This research focuses on knowing what are the moral messages contained in the video clip “Yura Yunita- Tutur batin